The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3201/eid1712.110371
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E Virus Antibodies in Blood Donors, France

Abstract: Using a validated sensitive assay, we found hepatitis E virus (HEV) IgG in 52.5% of voluntary blood donors in southwestern France. This fi nding suggests HEV is highly endemic to this region. The high HEV prevalence may refl ect local dietary practices, such as eating uncooked pork and game products. It is now recognized that hepatitis E virus infection is not confi ned to developing countries. HEV infection is a growing public health concern in industrialized countries where the disease is mainly autochthonou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

40
327
2
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 327 publications
(379 citation statements)
references
References 15 publications
40
327
2
10
Order By: Relevance
“…Other studies have shown that the seroprevalence among the general population varies widely. Thus, while using the same antibody assay (Wantai) as employed in this study, a seroprevalence of 16% was found in a cohort of healthy donors in the south-west of the United Kingdom (n=500) [24], whereas this percentage was as high as 53% in south-western France (n=512) [21]. Our findings presented in this study are in line with these earlier observations.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Other studies have shown that the seroprevalence among the general population varies widely. Thus, while using the same antibody assay (Wantai) as employed in this study, a seroprevalence of 16% was found in a cohort of healthy donors in the south-west of the United Kingdom (n=500) [24], whereas this percentage was as high as 53% in south-western France (n=512) [21]. Our findings presented in this study are in line with these earlier observations.…”
Section: Discussionsupporting
confidence: 82%
“…The MP/Genelabs assay used in this study was also employed in a recent study in 7,072 Dutch samples collected in 2006 and 2007, in which a seroprevalence of only 2.6% was found [20]. When compared to the Wantai assay used in this study, the MP/Genelabs assay was shown to be considerably less sensitive in PCR-proven HEV cases which explains the considerable higher seroprevalence found in this study [21,22]. In the study by Pischke et al, in a subgroup of AIH patients (n=123) anti-HEV was tested using the Wantai assay.…”
Section: Discussionmentioning
confidence: 91%
“…27 Thus, patients with an organ transplant are advised not to eat undercooked meat: HEV is only inactivated by temperatures >70 C. 28 In addition to the classical routes, HEV can be transmitted by blood transfusion, via the allograft, or by nosocomial transmission. Although, no case of HEV transmission via blood transfusion has been reported in the transplant population, 9 HEV seroprevalence in blood donors is high 29 and cases of HEV transmission via blood products have been reported in other populations. [30][31][32] Hence, if HEV infection is detected a few days after a blood transfusion, this mode of contamination should be investigated.…”
Section: Mode Of Hev Transmission Among Patients With a Sotmentioning
confidence: 96%
“…Częstotliwość występowania zakażeń u ludzi różni się w zależności od regionu świata. W Europie wynosi ona od 0,03% do 52% z najwyższym odsetkiem infekcji wśród osób pochodzących z terenów wiejskich, myśliwych lub mających kontakt ze zwierzętami uznanymi za rezerwuar wirusa (39). Seroprewalencja wzrasta wraz z wiekiem badanych osób i jest najwyższa (70%) w grupie pacjentów powyżej 58. roku życia (39).…”
Section: Replikacja Wirusa W Komórceunclassified
“…Wyniki badań serologicznych prowadzonych wśród hodowców świń, lekarzy weterynarii oraz pracowników leśnych dowodzą częstszej obecności anty-HEV IgG u osób z tych grup zawodowych. Niemniej jednak nie obserwuje się gwałtownego wzrostu zachorowań osób zawodowo narażonych na kontakt ze zwierzętami (7,27,39,42,64).…”
Section: Replikacja Wirusa W Komórceunclassified